"Estimating the recoverable value of in-situ building materials". (April 2023) - Mollaei, Aida; Bachmann, Chris; Haas, Carl
Highlights: Factors impacting the value of in-situ materials have been studied. A decision support tool based on an optimization model is developed for in-situ building material value estimation. Impact of key factors on value of-situ materials have been analyzed using the developed tool. Building component recovery through the optimization of EoL options can have high return on investments. Abstract: Construction, renovation and demolition of buildings in our cities is driving substantial material consumption and waste streams. They can be reduced by recovering in-situ materials from buildings with controlled demolition, disassembly, and deconstruction of components and materials. To do this, a decision support tool that can be used to estimate current recoverable environmental and market values from the owner's perspective of in-situ construction materials in a specific facility must be developed. Here, a linear programming optimization methodology is used that considers cost, value, duration, environmental impacts, and building component precedence in demolition and deconstruction activities. It helps choose the optimal combination of reuse, recycling and disposal options for those materials. The resulting decision support tool is functionally demonstrated on an institutional building to find the building components' optimal end-of-life alternatives to maximize the recovered value from the in-situ materials. Sensitivity analyses add further validation. Thus, this research supports the transition to a more circular economy in cities by making it easier to realize the full value of in-situ materials for planning, asset management, and demolition project bids. Graphical abstract: Image, graphical abstract